WEBOMETRICS RANKING: ANALYSIS OF CHANGES - Vladimir M. Galynsky (Высшее образование в России)
The paper substantiates the necessity of the presence of Russian and Belarusian universities in the world webometrics rankings. The author analyzes the changes in methodology of Webometrics Ranking (WRWU) in 2016. The new one of ranking parameters is transparent ranking: top universities by Google Scholar Citations. It is shown that only 2.7% of the Russian Federation universities have set up the profiles in Google Scholar, which will undoubtedly impede an integration ofthe Russian-speaking researchers into the world scientific community and, consequently, affect on reputation and the number of citations. General recommendations for advancement in webometrics rating is given. The article also touches upon the technique and the results of repositories rankings, which involved only 2% of Russian universities.